2005
DOI: 10.1186/1472-6882-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse analysis of potential cellular responsiveness to Johrei, a Japanese healing technique

Abstract: Background: Johrei is an alternative healing practice which involves the channeling of a purported universal healing energy to influence the health of another person. Despite little evidence to support the efficacy of such practices the use of such treatments is on the rise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…protective effect as compared to non-GBM brain cells. Based on the results, the inexpensive are based on an assumption that counts are dependent on the number of cells present [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…protective effect as compared to non-GBM brain cells. Based on the results, the inexpensive are based on an assumption that counts are dependent on the number of cells present [6].…”
Section: Discussionmentioning
confidence: 99%
“…Then, these data are converted to make a movie. This unique technique is used in various fields of cancer and stem cell biology for assessment of cell translation, division, and death [5,6]. Presently, several strategies are available for the treatment of GBM such as surgical techniques, radiotherapy, chemotherapy and electrochemotherapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…General applications in the life sciences include Grossman and Koops (2001), who fitted a polyexponential model to describe egg production in chickens, Knisley and Glen (1996) using polyexponential models in the context of firing of neurons, Mukerjee et al (2001), who use polyexponential models in the study of brain maturation, and Taft et al (2005), who fit a sum of two exponentials to data on cell division rates.…”
Section: Discussionmentioning
confidence: 99%
“…8 The last decade saw a growing interest in complementary and alternative medicine techniques, especially among patients with chronic pain disorders. [9][10][11] The popularity of alternative or complementary therapeutic modalities stems primarily from dissatisfaction with conventional therapeutic approaches. Whilst not specifically studied in NCCP, a study demonstrated a significant utilization of alternative medicine among patients with GERD.…”
Section: Introductionmentioning
confidence: 99%